Physiology and pathophysiology of marathon running: A narrative review - Braschler, L.; Nikolaidis, P. T.; Thuany, M.; Chlíbková, D.; Rosemann, T.; Weiss, K.; Wilhelm, M.; Knechtle, B. (Sports Medicine - Open, 2025)
Background Marathon training and running have many benefcial efects on human health and physical ftness; however, they also pose risks. To date, no comprehensive review regarding both the benefts and risks of marathon running on diferent organ systems has been published.